2010
DOI: 10.1038/onc.2010.350
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C promotes melanoma progression by maintaining the ABCB5-positive side population

Abstract: Tenascin-C (TNC) is highly expressed in melanoma; however, little is known about its functions. Recent studies indicate that TNC plays a role within the stem cell niche. We hypothesized that TNC creates a specific environment for melanoma cells to exhibit a stem cell-like phenotype, driving tumor growth and evading conventional therapies. TNC expression was strongly up-regulated in melanoma cells grown as 3D spheres (enriched for stem-like cells) when compared to adherent cells. Down-modulation of TNC by shRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 45 publications
(50 reference statements)
5
76
1
3
Order By: Relevance
“…76 The existence of a stem cell-like population in melanoma was additionally fortified by a recent study of the effect of the ECM glycoprotein tenascin-C on melanoma progression; these data demonstrated that tenascin-C in the microenvironment encouraged manifestation of a stem cell-like phenotype in melanoma cells that included the expression of ABCB5. 77 Most recently, melanoma cells that expressed the receptor activator of NF-kB (RANK) demonstrated enhanced tumorigenicity compared with RANK-negative melanoma cells in IL-2Rg À/À NOD/SCID mice. 78 Moreover, RANK was coexpressed with ABCB5 and CD133 on melanoma cells, and preferentially expressed by peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanomas compared with stage I melanoma patients.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…76 The existence of a stem cell-like population in melanoma was additionally fortified by a recent study of the effect of the ECM glycoprotein tenascin-C on melanoma progression; these data demonstrated that tenascin-C in the microenvironment encouraged manifestation of a stem cell-like phenotype in melanoma cells that included the expression of ABCB5. 77 Most recently, melanoma cells that expressed the receptor activator of NF-kB (RANK) demonstrated enhanced tumorigenicity compared with RANK-negative melanoma cells in IL-2Rg À/À NOD/SCID mice. 78 Moreover, RANK was coexpressed with ABCB5 and CD133 on melanoma cells, and preferentially expressed by peripheral circulating melanoma cells, primary melanomas, and metastases from stage IV melanomas compared with stage I melanoma patients.…”
Section: Stochastic Model Cancer Stem Cell Modelmentioning
confidence: 99%
“…mRNA was extracted from human NB cell lines HTLA-230 and GI-LI-N and human melanoma cell line MZ2-MEL [77] as positive control [51] using RNeasy Mini Kit from Qiagen (Qiagen GmbH, Hilden, Germany) and subjected to RT-PCR. Briefly, 1 µg of RNA was reverse transcribed using the RevertAid TM First Strand cDNA Synthesis kit (Fermentas Inc., Burlington, ON, Canada) following the instructions of the manufacturer.…”
Section: Real-time Qpcrmentioning
confidence: 99%
“…Tumor-derived TNC promotes or enhances the process of neovascularization in different tumor models [23][24][25][26][27][28]51].…”
Section: Orthotopic Nb Tumors Formed By Tnc + But Not Tnc − Htla-230 mentioning
confidence: 99%
“…In fact, studies undertaken on melanoma cellular models have shown that TNC expression was strongly up-regulated in melanoma cell growth-as 3D spheres enriched for stem-like cells when compared to in adherent cells (Fukunaga-Kalabis et al, 2010). As for other molecules present in the tumor microenvironment, it has been possible to identify TNC in the Figure 2.…”
Section: Tenascin Cmentioning
confidence: 99%